Ethics and opportunity costs: have NICE grasped the ethics of priority setting? - McMillan, J. (Journal of medical ethics, 2006)
The Social Value Judgments consultation document reveals NICE’s failure to understand its role in healthcare prioritisation The National Institute for Health and Clinical Excellence (NICE) has published a draft guideline, Social Value Judgments: Guidelines for the Institute and its Advisory Bodies (Social Value Judgments), which outlines the ethical framework that will guide its decision making in the future.1 NICE guidance has a profound effect upon the delivery of health care within the National Health Service (NHS) so it is crucial that an overarching guideline such as this is suited to the task that it needs to perform. In this paper we argue that NICE has misunderstood the way in which its advice fits into prioritisation decisions. This misunderstanding is amplified by its views about the ethical principles that should apply to prioritisation and, in particular, its failure to appreciate the role of fair processes in prioritisation. The national and international standing of NICE means that the definitive version of Social Value Judgments: Guidelines for the Institute and its Advisory Bodies is likely to have influence beyond the institute itself. There is much to welcome about the document, not least the acknowledgement that there are important ethical dimensions to NICE’s decision making. Indeed, the significance of the document lies in the fact that NICE is attempting to create an explicit ethical framework for funding decisions. There is, however, much that is of concern. Although John Harris has made some important points about the NICE position on age and sex,2 there are other important problems that need to be discussed. First, there appears to be confusion over the nature of the funding decisions taken by NICE and, as a result, the role of its guideline. It is of vital importance that professionals and public alike understand the precise nature of …